A New Approach to Responsible Entrepreneurship: Integrating Sustainability Into Business Practices - Dessy Marhandrie (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This study examining the transformative journey of entrepreneurs towards integrating sustainability into business practices. The review synthesizes current literature to elucidate motivations, challenges, strategies, and impacts associated with sustainable entrepreneurship. Key findings highlight how entrepreneurs respond to external pressures by adopting sustainable business models driven by ethical values and regulatory demands. Challenges such as financial constraints and regulatory complexities are addressed through innovative strategies like technology adoption and stakeholder collaborations. The review underscores that while initial costs may pose challenges, sustainable practices enhance long-term business resilience and stakeholder engagement. The study contributes to understanding the evolving landscape of sustainable entrepreneurship, emphasizing the shift towards proactive responsibility and its implications for business performance and societal well-being. Keywords , , ,